Effects of photodynamic therapy on the adhesive interface using two fiber posts cementation systems - Ramos, Anna Thereza Peroba Rezende [UNESP]; Belizário, Lauriê Garcia [UNESP]; Jordão-Basso, Keren Cristina Fagundes [UNESP]; Shinohara, André Luis; Kuga, Milton Carlos [UNESP] (Elsevier, 2018)
Introduction: Photodynamic therapy (PDT) can be employed for prosthetic space decontamination; however, its effects on adhesion of glass-fiber posts cementation systems are still unclear. Purpose: The aim of this study was to evaluate the effects of photodynamic therapy (PDT) on the adhesive interface between the dentin and different glass-fiber post cementation systems using a self-adhesive resin cement (RelyX U200) or a glass ionomer cement (Gold Label 1). Method: Forty human canine roots were endodontically-treated and prepared for fiber post. The roots were divided into four groups (n = 10), according to the PDT use and cementation protocol, as follow: G1- RelyX U200; G2: Gold Label 1; G3: PDT + RelyX U200; and G4: PDT + Gold Label 1. Afterwards, the roots were cross-sectioned and specimens from the cervical, middle and apical thirds of the post space were obtained and submitted to the push-out test. After that, the dentinal penetrability of the cementation protocol was assessed using laser confocal microscopy. Current results: No significant differences were found in the bond strength values among the groups in all thirds (P > 0.05). G2 and G4 presented lower dentinal penetrability than the other groups, only in the cervical third (P < 0.05). Conclusion: Photodynamic therapy didn't present effects on the bonding interface between root dentin and fiber post cementation systems in both RelyX U200 and Gold Label 1, which were similar to each other.
Keywords: Antimicroial photodynamic therapy; Fiber posts; Glass-ionomer cement; Photodynamic therapy; Self-adhesive cement